Estimulação magnética transespinal theta-burst associada ao treinamento em esteira na mobilidade funcional de pessoas com Doença de Parkinson : estudo piloto randomizado cruzado - Gomes, Maria Luisa Andrade (2024)
Introduction: Intermittent Theta-Burst Trans-spinal Stimulation is an innovative and promising intervention with the potential to enhance neuronal plasticity and improve gait in individuals with Parkinson's Disease. Objective: To compare the effectiveness of two protocols of intermittent Theta-Burst Trans-spinal Stimulation—one with 3,600 pulses and another with 1,200 pulses—both followed by treadmill training, on functional mobility in individuals with Parkinson's Disease. Method: This is a single-blind, controlled, two-period crossover pilot study. Ten participants (5 to receive treatment A first, and 5 to receive treatment B first) with idiopathic Parkinson's disease between modified Hoehn & Yahr stages 1.5 to 3 and mean age 61.4 ± 9.71 completed the study. All participants received two treatments with five sessions each: A (60 trains of stimulation, 3,600 pulses) and B (20 trains of stimulation, 1,200 pulses), both followed by treadmill training for 15 minutes, separated by a period of 4 weeks. The primary outcome was functional mobility, and the secondary outcomes were dual-task functional mobility, gait speed, motor function, quality of life, non-motor symptoms and perceived global change. Results: For functional mobility, the treatments showed similar performances (p=0.404; F=0.773). No significant differences were observed in gait speed (p=0.373; F=0.37). Quality of life (p=0.208; F=1.88) and non-motor symptoms (p=0.859; F=0.03) were also similar. However, there was a significant difference in motor function (p=0.020; F=8.261) favoring Treatment A. Treatment A had a greater positive impact on gait performance perception (90% of participants) compared to Treatment B (50%), and on walking safety (50% for A and 30% for B). No serious adverse events were reported. Conclusions: This pilot study suggests that both stimulation protocols combined with treadmill training can modify the functional mobility of people with Parkinson's disease. However, the more intensive protocol seems to offer greater benefits for motor function. Further research is needed to substantiate these results. Brazilian Registry of Clinical Trials (RBR-5r6pm9x).